Efektivitas Penggunaan Media Pembelajaran Audiovisual dalam Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran Fiqih di Kelas X MIPA 4 Madrasah Aliyah Islamic Centre Bin Baz Yogyakarta - Tyan Rahayu (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effectiveness of audiovisual learning media in improving fiqh learning outcomes of grade X students at Madrasah Aliyah Islamic Centre Bin Baz Yogyakarta. The background of this research is the importance of innovation in the learning process so that fiqh material can be delivered optimally and attract students’ learning interest. The method used is a quantitative approach with a quasi-experimental design using two classes, namely the experimental class using audiovisual media and the control class using conventional methods. The hypothesis test results using the t-test showed a significance value of 0.074, which means there is a significant influence of the use of audiovisual media on fiqh learning outcomes. Furthermore, the N-Gain test showed that the experimental class had an average learning outcome increase of 67.73, categorized as quite effective, while the control class only obtained 45.61, categorized as less effective. Thus, the use of audiovisual learning media is proven to improve students’ understanding and learning outcomes in fiqh subjects. These findings are expected to serve as a reference for the development of more interactive and effective learning methods in madrasah environments.